Catalytic Conversion of Residual Palm Oil in Spent Bleaching Earth (SBE) By HZSM-5 Zeolite based-Catalysts - Mohd Lukman Musa; Ramli Mat; Tuan Amran Tuan Abdullah (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
Bleaching earth is used to remove colour, phospholipids, oxidized products, metals and residual gums in the palm oil process refinery. Once adsorption process end, the spent bleaching earth (SBE) which contains approximately 20-40 wt. % of the adsorbed oil was usually disposed to landfills. The oil content in SBE was recovered by catalytic cracking using transition metal (Cu, Zn, Cr, and Ni) doped HZSM-5 zeolite in a batch reactor (pyrolysis zone) and fixed bed reactor (catalyst bed). The 5 wt. % of each metallic was introduced in HZSM-5 zeolite using incipient wetness impregnation method. The main objective of this study was to investigate the performance of modified HZSM-5 zeolite for cracking of residual oil in SBE. The physicochemical properties of the catalysts were characterized    using XRD, FTIR, Nitrogen adsorption, and TPD-NH3.  Liquid biofuel obtained from cracking was analyzed by GC-MS. The incorporation of metallic loaded on HZSM-5 zeolite has reduced the surface area of the catalyst that gives a significant impact to the catalytic behavior. The Ni/HZSM-5 zeolite exhibited the highest yields of alkenes as compared to others but slightly decreases the yield of alkanes whereas in contrast with the Cr/HZSM-5, the obtained alkanes were found higher than that of alkenes. In addition, the Cr/HZSM-5 and Ni/HZSM-5 favored the conversion of polycyclic aromatics to mono-aromatics, whereas parent HZSM-5 catalyst favored the formation of poly-aromatics. These results indicated that the metal loaded on HZSM-5 can promote the cracking of heavy fractions to lighter hydrocarbon thus can be used for cracking oil in SBE.